2001
DOI: 10.1053/rapm.2001.25069
|View full text |Cite
|
Sign up to set email alerts
|

The effect of distance from injection site to the brainstem using spinal sufentanil

Abstract: Our results suggest that sufentanil migrates relatively large distances in the IT space. Injection site (distance from the brainstem) appears to be a prominent factor in determining brainstem concentrations and subsequent respiratory depression after spinal administration. Reg Anesth Pain Med 2001;26:306-309.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 22 publications
0
18
0
4
Order By: Relevance
“…Ferouz et al 4 reported that IT injection of sufentanil resulted in similarly rapid extension of hypoalgesia tested by pinprick to upper thoracic or cervical dermatomes of women in labor. Swenson et al 12 demonstrated a rapid rostral spread of sufentanil after IT injection in sheep. In contrast, Hansdottir et al 15 stated that after an IT injection in humans, sufentanil is rapidly cleared from cerebrospinal fluid and absorbed by plasma, with a mean residence time much longer in plasma (7 hours) than in cerebrospinal fluid (1 hour).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferouz et al 4 reported that IT injection of sufentanil resulted in similarly rapid extension of hypoalgesia tested by pinprick to upper thoracic or cervical dermatomes of women in labor. Swenson et al 12 demonstrated a rapid rostral spread of sufentanil after IT injection in sheep. In contrast, Hansdottir et al 15 stated that after an IT injection in humans, sufentanil is rapidly cleared from cerebrospinal fluid and absorbed by plasma, with a mean residence time much longer in plasma (7 hours) than in cerebrospinal fluid (1 hour).…”
Section: Discussionmentioning
confidence: 99%
“…5 Sufentanil may also migrate rostrally via the cerebrospinal fluid and reach supraspinal opioid receptors. Cephalad migration is supported by human 2,4 and animal studies 12,13 and may be favored by cerebrospinal fluid bulk movement, derived from the movement of the brain and spinal cord as they expand and contract during cardiac systole and diastole. 14 On the other hand, sufentanil clearance into spinal cord vessels and diffusion across the meningeal membranes to the epidural space, which causes a supraspinal analgesia by systemic uptake, must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…However, sufentanil may compromise ventilation as a result of rapid systemic absorption. Sufentanil also may migrate to relatively long distances in cerebrospinal fluid to reach the respiratory center [91]. Thus, close monitoring and prompt treatment of adverse effects is essential when any epidural opioid is administered.…”
Section: Epidural Opioidsmentioning
confidence: 99%
“…Respiratory depression may develop due to rapid absorption from the application site or cephalad spread of opioids in cerebrospinal fluid into the respiratory center [91]. Therefore, the respiratory function of children should be monitored closely, not only after opioid administration, but also for several hours thereafter.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…The current study by Swenson et al, 1 which demonstrates a remarkable distance and rapidity of spread in CSF of the extremely lipid soluble opioid, sufentanil, after intrathecal injection, illustrates several facets of this commonly believed myth regarding these drugs.…”
mentioning
confidence: 56%